THE ERA OF THE MARTYRS IN THE HISTORICAL MEMORY OF THE SYRIAN CHRISTIANS (LATE IV – FIRST HALF OF THE V CENTURY) - Vodko, Vladyslav I. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2020)
This research is aimed at studying the nature of Christian Syrians’ historical memory about the era of the martyrs on the Syrian territory for the period between the end of the IV century and the first half of the V century. That was the time when Christianity was developing as the state religion in the Roman Empire. We tried to figure out how the historical memory of the martyrs reflects the peculiarities of the cultural identity of the Syrians and their attitude to representatives of other ethnic groups. It is the first analysis of Syrians’ historical memory about the era of the martyrs. It is also a systematic review of the main social and ideological functions that were inherent in Syrians’ historical memory about the era of the martyrs (for the period between the late IV century and the first half of the V century). The research resulted in several conclusions about the specificities of the Syrian identity of the designated period. The Christian – Pagan polemic in Syria, in its turn, was considered through the prism of historical memory. Conclusions. The era of early Christian martyrs in Syrian historical memory performed the whole set of cultural, social and ideological functions. The historical memory of the martyrs was an important part of the religious identity of the Syrians who lived on the territory of two warring states, namely Persia and Rome. Representatives of the Syrian church of the designated period emphasized that their church received a significant boost thanks to many martyrs, which became a serious argument in theological disputes and helped to strengthen the regional identity the Antioch school of theology representatives. This school, in its turn, was going through hard times in the 30–40s of V century because of accusations of heresy. The historical memory of the era of the martyrs reflects the issues of the polemic of Christians with their gradually dying paganism (these issues are relevant for the designated period). The texts which constitute a reception of the era of the martyrs often reflect certain socio-economic problems and ethnic contradictions. For instance, Jews are accused of persecuting Christian Syrians in Persia. They say that the Persian ruler increased taxes for Christian Syrians during their persecution. Legends about persecutions in Persia are trying to explain the non-religious causes of persecution and (implicitly) to create some model of behavior that would allow to avoid similar problems for the Christian community in the future.